The Online Froissart : A digital edition of The Chronicles of Jean Froissart - University of Sheffield - Humanities Research Institute (2010)
"Jean Froissart’s Chroniques cover the period from around 1326 to around 1400 and are the single most important contemporary prose narrative about the first part of the Hundred Years’ War. More than 150 manuscript volumes containing the Chronicles have survived in more than 30 different libraries across Europe and North America. Of the four Books of the Chronicles the first three exist in substantially different versions." [self-description]